Biomaterials science an introduction to materials in medicine - Ratner, B. D. (Buddy D.), 1947- ([S.l.] : Academic Press, 2013)
The most comprehensive textbook on the principles and applications of all classes of biomaterials Edited by four of the leaders in the biomaterials field today and fully endorsed and supported by the Society for Biomaterials Revised and expanded, key new topics include: tissue engineering, drug delivery systems, new materials, and new clinical applications and pertinent translational and commercial considerationsNew teaching and learning material; a structured curriculum in biomaterials education Biomaterials have a profound impact on human health. They also impact much ongoing research and development into new and improved implants and devices in both medicine and biotechnology. The third edition of this renowned and best-selling title is the most comprehensive and up-to-date single text on all aspects of biomaterials science. It provides a balanced, insightful approach to learning the science and technology of biomaterials, and acts as a key reference for clinicians and scientists, both academic and corporate, who have involvement in the applications of materials in medicine. This resource is ideal for undergraduate and graduate students, and investigators and educators in biomedical engineering sciences, and medicine. Over 29,000 copies sold, this is the most comprehensive coverage of principles and applications of all classes of biomaterials: 'the only such text that currently covers this area comprehensively' - Materials Today Edited by four of the best-known figures in the biomaterials field today; fully endorsed and supported by the Society for Biomaterials Fully revised and expanded, key new topics include of tissue engineering, drug delivery systems, and new clinical applications, with new teaching and learning material throughout, end of chapter exercises, assignments and case studies; and a downloadable image bank. The new edition is printed in full color throughout, with new high-quality artwork .
Preface -- How to Use This Text -- Introduction -- Part 1. Materials Science and Engineering -- Section 1.1. Properties of Materials -- Section 1.2. Classes of Materials Used in Medicine -- Part 2. Biology and Medicine -- Section 2.1. Some Background Concepts -- Section 2.2. Host Reactions to Biomaterials and Their Evaluation -- Section 2.3. Biological Testing of Biomaterials -- Section 2.4. Degradation of Materials in the Biological Environment -- Section 2.5. Applications of Biomaterials -- Section 2.6. Applications of Biomaterials in Functional Tissue Engineering -- Part 3. Practical Aspects of Biomaterials -- Section 3.1. Implants, Devices, and Biomaterials: Special Considerations -- Section 3.2. Voluntary Standards, Regulatory Compliance and Non-Technical Issues -- Appendix A: Properties of Biological Fluids -- Appendix B: Properties of Soft Materials -- Appendix C: Chemical Compositions of Metals Used for Implants -- Appendix D: The Biomaterials Literature.
Includes bibliographical references and index.
Keywords: Biocompatible Materials; Biomedical materials; Anti-infective agents; Electronic books